PENEGAKAN ATURAN HUKUM TERHADAP PELAKU PENGULANGAN TINDAK PIDANA KORUPSI - Gunawan, Tri Deri; Unu Herlambang (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2024)
Corruption is a crucial issue, where repeat offenses (recidivism) reflect the weak deterrent effect of the current punishment system. This study aims to analyze the effectiveness of law enforcement against repeat offenders of corruption and to review the possibility of applying the death penalty in accordance with the provisions of Article 2 paragraph (2) of the Anti-Corruption Law. The study uses a normative juridical approach, with data collection techniques through literature study. The analysis was conducted using the theory of law enforcement systems and the theory of punishment to assess the extent to which the legal system is capable of creating certainty, justice, and legal benefits in the context of eradicating corruption. The results of the study show that although legal provisions have provided room for the imposition of maximum penalties, their implementation is still weak and has not touched on cases of repetition that are classified as serious. Therefore, political courage and consistency in law enforcement are needed in order to achieve the objectives of the law optimally.